Running economy and lower-limb anthropometry in adult male Kenyan and Danish middle- and long-distance runners and in untrained adolescents - Larsen, H. B.; Boit, M. K.; Adamsen, M. L.; Madsen, F.; Berg, R. M. G.; Hanel, B. (Experimental Physiology, 2026)
Kenyan athletes have dominated competitive middle- and long-distance running for more than half a century, a phenomenon suggested to be attributable, at least in part, to superior running economy. Given that lower-leg anthropometry is an important determinant of running economy, a key contributor to the athletic performance of Kenyan runners is thought to be slender lower legs. Running economy and lower-leg anthropometrics, including relative lower-leg length and mean lower-leg thickness, were measured in adult middle- to long-distance runners, including 12 Kenyan elite and 29 sub-elite runners, and 20 Danish elite and 37 sub-elite runners. Additionally, 46 untrained Kenyan and 30 untrained Danish adolescents were included. Among adult runners, the oxygen cost of running was 33.61 mL kg-0.75 km-1 lower in Kenyans compared with Danes [95% confidence interval (CI): 18.63, 48.59; p < 0.0001] and increased by 2.20 mL kg-0.75 km-1 per centimetre squared increase in lower-leg cross-sectional area (95% CI: 1.03, 3.37; p = 0.0005). In untrained adolescents, the oxygen cost of running was 44.82 mL kg-0.75 km-1 lower (95% CI: 21.99, 67.64; p = 0.0002) and increased by 1.75 mL kg-0.75 km-1 per centimetre squared increase in lower-leg cross-sectional area (95% CI: 0.18, 3.32; p = 0.0294). Slender lower legs are favourably associated with superior running economy and might contribute to the dominance of Kenyan athletes in competitive middle- to long-distance running.